2020
DOI: 10.1002/esp.4962
|View full text |Cite
|
Sign up to set email alerts
|

Sand settling through bedform‐generated turbulence in rivers

Abstract: Fluvial bedforms generate a turbulent wake that can impact suspended-sediment settling in the passing flow. This impact has implications for local suspended-sediment transport, bedform stability, and channel evolution; however, it is typically not well-considered in geomorphologic models. Our study uses a three-dimensional OpenFOAM hydrodynamic and particle-tracking model to investigate how turbulence generated from bedforms and the channel bed influences medium sand-sized particle settling, in terms of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 127 publications
(216 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, as shown in Figure 3, the riverbed mainly consists of sand and has many complex braided flow sections, as shown in Figure 3c,d. Notably, sand dunes are formed in the entire section, which can increase the residence time of the solute owing to the dynamic interaction between the hyporheic zone and the main flow area [36][37][38]. The geomorphological features of Gam Creek indicate the existence of flow stagnation zones and the storage effect; additionally, this river has been used as an appropriate study site to verify the storage effect reproduced by the model, as detailed by Kim et al [7].…”
Section: Field Experimentsmentioning
confidence: 99%
“…Furthermore, as shown in Figure 3, the riverbed mainly consists of sand and has many complex braided flow sections, as shown in Figure 3c,d. Notably, sand dunes are formed in the entire section, which can increase the residence time of the solute owing to the dynamic interaction between the hyporheic zone and the main flow area [36][37][38]. The geomorphological features of Gam Creek indicate the existence of flow stagnation zones and the storage effect; additionally, this river has been used as an appropriate study site to verify the storage effect reproduced by the model, as detailed by Kim et al [7].…”
Section: Field Experimentsmentioning
confidence: 99%
“…Because of the interaction between flow and a complex bed shape, the movement of sand grains above a bedform differs from that of sand grains above a flat bed. Through numerical modelling, Yuill et al (2020) showed that settling velocities were reduced by up to 50% above bedforms compared with over a flat bed. This is due to the eddies generated in the bedform wake and, to a lesser extent, to turbulence arising from velocity shear at the bed which maintain sediment in suspension over the bedform lee side and trough.…”
Section: Small-scale Bedform Dynamicsmentioning
confidence: 99%